Respuestas

¡La mejor respuesta!
2012-09-14T02:25:22+02:00

f(x)=log [(x-1)(x+3)]

dominio:

(x-1)(x+3)>0

x=1

x=-3

<----------|-----------|--------->

            -3               1

Dom=<-00,-3> unido<1.+00>

 

raices:

log [(x-1)(x+3)]=0

(x-1)(x+3)=1

x^2+x-3=1

x^2+x-4=0

x=(-1+-√(1+4*4))/2

x=-1.56  ó  x=1.56

 

 

 

2012-09-14T03:31:44+02:00

f(x)=log [(x-1)(x+3)]

dominio:

(x-1)(x+3)>0

x=1

x=-3

<----------|-----------|--------->

            -3               1

Dom=<-00,-3> unido<1.+00>

 

raices:

log [(x-1)(x+3)]=0

(x-1)(x+3)=1

x^2+x-3=1

x^2+x-4=0

x=(-1+-√(1+4*4))/2

x=-1.56  ó  x=1.56

 

bueno es lo k masomenos entiendo xD